A study of secondary three students' language anxiety - Han, Lee Yen. (2008)
This study sets out to investigate the language anxiety experienced by 56 secondary 3 students while learning English. The extent to which they experience anxiety, the most anxiety-arousing aspect of language learning, the relation between language anxiety and their sense of self-efficacy and the sources of language anxiety are explored.